Anaerobic fermentation of rice bran with rumen liquor for reducing their fiber components to use as chicken feed. Issue 4 (April 2022) - Debi, Momota Rani; Wichert, Brigitta A.; Liesegang, Annette
Abstract: Rice bran is a very cheap and abundant agricultural by-product in rice producing countries. Additionally, many developing countries used these by products as poultry feed. Rice bran (RB) contains high fiber and chicken is not capable to digest those fibrous feed effectively, resulting in low production performance. The main objectives of this study were to decrease fiber components of RB through fermentation by adding rumen liquor to increase their utilization efficacy in chicken. A single-step fermentation of RB was conducted for 12 h (n = 6) under anaerobic conditions, maintaining proper temperature and ideal pH. Rice bran, buffer substances, and rumen liquor were mixed at the ratio of 1:2:3, respectively. The fresh and fermented rice brans were examined for the content of acid detergent fiber (ADF), crude fiber (CF), dry matter (DM), crude protein (CP), neutral detergent fiber (NDF) and acid detergent lignin (ADL). Other fiber components were determined by substracting the value of ADL from ADF (celluloses) and ADF from NDF (hemicelluloses), respectively. One-way analysis of variance was done to compare the mean nutrient components followed by Tukey's multiple comparison tests at P < 0.05. The pH of fermented brans was decreased with growing fermentation period but appropriate pH was maintained due to the developed protocol. After fermentation, the fiber components of RB were reduced significantly (P < 0.05). However, CP component was not altered significantly after the fermentation of brans. The NDF, ADF, cellulose, hemicellulose contents were reduced by 16.2 ± 0.52, 7.2 ± 0.32, 20.0 ± 0.38 and 23.6 ± 0.54%, respectively compared to the fresh brans. As the fiber content reduced significantly after fermentation that clearly, increases the usability of brans as chicken feed. Abstract : Developing countries, Fermentation, Fiber content, Chicken nutrition, Rice bran, Rumen microbes.